The deadly ideas of neoliberalism : how the IMF has undermined public health and the fight against AIDS - Rowden, Rick. (London : Zed Books, 2009)
'The Deadly Ideas of Neoliberalism explores the history of and current collision between two of the major global phenomena that have characterized the last 30 years: the spread of HIV/AIDS and other diseases of poverty and the ascendancy of neoliberal economic ideas. The book explains not only how IMF policies of restrictive spending have exacerbated public health problems in developing countries, in particular the HIV/AIDS crisis, but also how such issues cannot be resolved under these economic policies. It also suggests how mounting global frustration about this inability to adequately address HIV/AIDS will ultimately lead to challenges to the dominant neoliberal ideas, as other more effective economic ideas for increasing public spending are sought. In stark, powerful terms, Rowden offers a unique and in-depth critique of development economics, the political economy dynamics of global foreign aid and health institutions, and how these seemingly abstract factors play out in the real world - from the highest levels of global institutions to African finance and health ministries to rural health outposts in the countryside of developing nations, and back again.' -- Publisher's description.
Includes bibliographical references (p. [211]-235) and index.
Keywords: International Monetary Fund; International Monetary Fund; AIDS (Disease) -- Prevention -- Finance -- Economic aspects -- Developing countries; Neoliberalism -- Economic aspects; AIDS (Disease) -- Treatment -- Finance -- Economic aspects -- Developing countries; Public health -- Economic aspects -- Developing countries; Economic assistance -- Developing countries